2017
DOI: 10.1186/s13256-017-1315-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of body mass index to metabolic syndrome risk factors in Syrian adolescents

Abstract: Background: Obesity has become a serious epidemic health problem in both developing and developed countries. There is much evidence that obesity among adolescents contributed significantly to the development of type 2 diabetes and coronary heart disease in adulthood. Very limited information exists on the prevalence of overweight, obesity, and associated metabolic risk factors among Syrian adolescents. Therefore, the purpose of this study was to determine the relationship between obesity determined by body mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
3
6
1
Order By: Relevance
“…On the other hand, Al‐Bachir et al, in their study with a Syrian adolescent population, concluded that BMI, despite showing values of AUC lower than those obtained in our study, is still a powerful discriminator for abdominal obesity. In regard to C‐Index, in our study, this index resulted to be a less reliable discriminator for abdominal obesity than AVI, WC, BMI and BRI.…”
Section: Discussioncontrasting
confidence: 94%
“…On the other hand, Al‐Bachir et al, in their study with a Syrian adolescent population, concluded that BMI, despite showing values of AUC lower than those obtained in our study, is still a powerful discriminator for abdominal obesity. In regard to C‐Index, in our study, this index resulted to be a less reliable discriminator for abdominal obesity than AVI, WC, BMI and BRI.…”
Section: Discussioncontrasting
confidence: 94%
“…As in our study, classical lichen ruber planus is the most frequently reported lichen subtype in the literature 10,13 . Cutaneous involvement in the lichen planus is 70%‐75%, and it was found to be very close to the literature in our study 1 …”
Section: Discussionsupporting
confidence: 83%
“…But the data on the relationship between LP and MS are limited 2,4,7,8 . It has been shown to have a strong association between body mass index and metabolic syndrome components 7,8,13 . Body mass index in lichen planus patients was studied in a limited number of studies, Kar et al 7 found an average of 24.3, and Arias‐Santiago et al 8 found an average of 26.4.…”
Section: Discussionmentioning
confidence: 99%
“…Other subject characteristics in terms of BMI showed that most of the subjects had obesity in nutritional status, with obesity I was found at 40% of the subjects and obesity II at 36.3%. The overweight and obesity in BMI category are related to the metabolic syndrome components, which is in line with research in Syria on the adolescent subjects who were 18-19 years (28). There are various medical and psychosocial complications related to overweight and obesity among adolescents such as hypertension, dyslipidemia, insulin resistance, type 2 diabetes mellitus, sleep disorders and other respiratory disorders (1).…”
Section: Research Subjects Characteristicssupporting
confidence: 64%